Kojic acid reverses LPS-induced neuroinflammation and cognitive impairment by regulating the TLR4/NF-κB signaling pathway - Ali, Waqar; Choe, Kyonghwan; Park, Jun Sung; Ahmad, Riaz; Park, Hyun Young; Kang, Min Hwa; Park, Tae Ju; Kim, Myeong Ok (Frontiers in Pharmacology, 2024)
Intense neuroinflammation contributes to neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease. Lipopolysaccharides (LPSs) are an integral part of the cell wall of Gram-negative bacteria that act as pathogen-associated molecular patterns (PAMPs) and potentially activate the central nervous system’s (CNS) immune system. Microglial cells are the local macrophages of the CNS and have the potential to induce and control neuroinflammation. This study aims to evaluate the anti-inflammatory and antioxidant effect of kojic acid against the toxic effects of LPSs, such as neuroinflammation-induced neurodegeneration and cognitive decline. The C57BL/6N mice were subjected to LPS injection for 2 weeks on alternate days (each mouse received 0.25 mg/kg/i.p. for a total of seven doses), and kojic acid was administered orally for 3 weeks consecutively (50 mg/kg/mouse, p. o). Bacterial endotoxins, or LPSs, are directly attached to TLR4 surface receptors of microglia and astrocytes and alter the cellular metabolism of immune cells. Intraperitoneal injection of LPS triggers the toll-like receptor 4 (TLR4), phospho-nuclear factor kappa B (p-NFκB), and phospho-c-Jun n-terminal kinase (p-JNK) protein expressions in the LPS-treated group, but these expression levels were significantly downregulated in the LPS + KA-treated mice brains. Prolong neuroinflammation leads to the generation of reactive oxygen species (ROS) followed by a decrease in nuclear factor erythroid-2-related factor 2 (Nrf2) and the enzyme hemeoxygenase 1 (HO-1) expression in LPS-subjected mouse brains. Interestingly, the levels of both Nrf-2 and HO-1 increased in the LPS + KA-treated mice group. In addition, kojic acid inhibited LPS-induced TNF-α and IL-1β production in mouse brains. These results indicated that kojic acid may suppress LPS-induced neuroinflammation and oxidative stress in male wild-type mice brains (in both the cortex and the hippocampus) by regulating the TLR4/NF-κB signaling pathway.